Significant Relationship between Anxiety Level and Oral Communication Performances: The Case of English Education Learners - Obert Janitra, Muhammad Jibril; Anwar, Khoirul (New Language Dimensions, 2022)
This study was conducted to find a correlation between students’ anxiety level and their relation to speaking performances, a quantitative research design using correlation method was used in conjunction with SPSS software to determine the connection between both variables. The method of anxiety data collection was accomplished through online FLCAS questionnaires with participants from English Education major learners from Universitas Muhammadiyah Gresik in the fourth semester, all which would be then correlated to their final speaking score provided by the lecturer. The result found that there is a significant correlation between EFL Anxiety and students’ speaking performances with r= -.702 and p= .000. Therefore, it can be claimed that N0 was rejected while Na was accepted. When compared to results from previous studies on anxiety from non-English department, this shows that anxiety also negatively affect learners who enrolled in English specialized major, and not limited to learners who need to participate English lesson in compulsory class.